Perceptions of Policing: Improving Communication in Local Communities. (December 2014) - Bain, Andy; Robinson, Bryan K.; Conser, Jim
Public perceptions of policing have provided a good deal of concern in recent years. However, there is also a growing body of evidence that suggests that part of the issue for policing local communities may stem from an ability to communicate effectively with the local populace. This article discusses the role of public perception and identifies a number of key factors implicit to the experience of policing. These include fairness in policing, media representation and the use of new (social) media in order to recognise and support the changing demographic in a local population. Among our conclusions, we suggest that further investment is needed in new media in order to provide for a positive front-facing service, aimed at engaging younger — often at-risk — populations, that become the future consumers of service.